Spontaneous wrinkling pattern of a constrained thin film membrane - Xi Chen (APPLIED PHYSICS A-MATERIALS SCIENCE & PROCESSING, 2012)
The wrinkling morphology of an inhomogeneously constrained thin film membrane is explored using finite element simulations, where a small circular area in a thin sheet undergoes expansion, and buckles emerge due to differential in-plane deformation. The local wrinkling patterns are characterized by the normalized circular (inner) area size, the modulus mismatch between the inner and outer regions, and the normalized stress in the inner area. As the stress increases, the morphology transits from ripple-like to petal-like and finally to a branched pattern. Through parametric studies, the effect of the governing variables on the pattern evolution, wave number, and maximum deflection is discussed. The model is used to qualitatively explain the delamination/blister morphology observed in thin film/substrate systems. The study has the potential of inspiring new fabrication techniques based on mechanical self-assembly.
Keywords: Thin Sheet; Ripple Wave; Normalize Stress Level; Circumferential Wave Number; Hydrofluoric Acid Solution